Analysis of the transition from pre-primary to primary: four studies: St. Lucia, St. Vincent & the Grenadines, Guyana, Jamaica - Michael, Jennifer (CARNEID St. MichaelBB)
Focuses on the current status of the pre-school and early primary units within the systems of education in each territory, and the circumstances which influence the transition of children from one unit to the other.